1998
DOI: 10.1021/jp9808328
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Oxidation of 1,2,5-Trimethylpyrrole:  Kinetic, Spectroscopic, and Electrochemical Studies

Abstract: The oxidation of 1,2,5-trimethylpyrrole (TMP) in aqueous and organic solvents is studied by various techniques. Heating oxygenated chlorobenzene solutions of TMP results in autoxidation that is initiated via reaction of TMP with O2 and partly propagated via oxidation of TMP by a TMP-derived peroxyl radical. In radiolytic experiments, TMP is oxidized rapidly by Br2 •- (k = 2.3 × 109 L mol-1 s-1), I2 •- (k = 5.1 × 108 L mol-1 s-1), CCl3O2 • (k = 5 × 108 L mol-1 s-1), and N3 • radicals in aqueous solutions and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…We have previously proposed that electron-rich aromatic molecules such as pyrroles, 11,12 indoles, 13 and carbazoles can be thermally promoted to react directly with molecular oxygen. [14][15][16] It is conceivable that such chemistry could ultimately lead to production of a high concentration of peroxyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously proposed that electron-rich aromatic molecules such as pyrroles, 11,12 indoles, 13 and carbazoles can be thermally promoted to react directly with molecular oxygen. [14][15][16] It is conceivable that such chemistry could ultimately lead to production of a high concentration of peroxyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The (EDOT-OH)C hydroxyl adduct as well as the EDOT + C radical cation subsequently undergo a second-order radical-radical reaction with themselves to produce EDOT dimers, as observed experimentally in this work and as reported in the case of both thiophene systems [32] and pyrrole derivatives. [35] In the field of conducting polymers, experiments concerning the photodegradation of polythiophene-based polymers demonstrated in the same way that HOC radicals lead to hydroxyl adducts, whereas N 3 C species give cation radicals of the polymers. [47] Given that radiation-induced polymerization proceeds through a recurrent step-by-step oxidation mechanism, both HOC and N 3 C radicals should react successively on EDOT dimers and then on oligomers to produce continuously hydroxyl adducts in the case of HOC and radical cations in the case of N 3 C. Then, one can expect the exclusive presence of hydroxyl groups in the HOC-induced radiosynthesized PEDOT polymers.…”
Section: Chemical Characterization Of Pedot-oh and Pedot-nmentioning
confidence: 98%
“…[32] In agreement with all of the previous results, it was found that HOC radicals add preferentially to the a position in thiophene (Th) to give (ThÀ OH)C adducts. [35] In our case and according to the literature, EDOT monomers should then be oxidized by HOC and N 3 C radicals according to the two following pathways [Eqs. [35] In our case and according to the literature, EDOT monomers should then be oxidized by HOC and N 3 C radicals according to the two following pathways [Eqs.…”
Section: Chemical Characterization Of Pedot-oh and Pedot-nmentioning
confidence: 99%
See 2 more Smart Citations